EPV 2. Spreading patterns of behavioral variant frontotemporal dementia: Analysis of longitudinal in vivo diffusion tensor imaging data. Issue 9 (September 2016) - Müller, H.-P.; Schroeter, M.; Anderl-Straub, S.; Uttner, I.; Tredici, K. Del; Otto, M.; Ludolph, A.C.; Kassubek, J.
Abstract : Introduction: Recently, the characteristic longitudinal distribution pattern of the underlying phosphorylated TDP-43 (pTDP-43) pathology in the behavioral variant of frontotemporal dementia (bvFTD) across specific brain regions was described (Brettschneider et al., 2013 ). The aim of the present study was the transfer of these neuropathological findings to a diffusion tensor imaging (DTI)-based in vivo staging protocol. Methods: Thirty-one bvFTD patients and 49 controls underwent DTI in a bicentric study design. Out of these, 14 bvFTD patients and 17 controls had a follow-up scan after 12 months. A second follow-up scan was performed in 4 bvFTD patients and in 7 controls, again after 12 months. Cross-sectional and longitudinal alterations were assessed by a two-fold analysis, i.e. voxelwise comparison of fractional anisotropy (FA) maps and a tract of interest-based (TOI) approach, which identifies tract structures that could be assigned to brain regions associated with disease progression (Kassubek et al., 2014 ). Results: Cross-sectional whole brain-based spatial statistics showed white matter alterations predominantly in the frontal lobes but no longitudinal alterations. The TOIs of bvFTD-stages 1 and 2 (uncinate fascicle – bvFTD-pattern I; corticostriatal pathway – bvFTD-pattern II) showed highly significant differences between bvFTD patients and controls. The corticospinal tract-associated TOI (bvFTD-pattern III) did not differ between groups in this group, whereas the differences in the optic radiation (bvFTD-pattern IV) were significant. Longitudinal TOI analysis allowed for individual patient categorization of one subgroup according to the pTDP-43 staging scheme. Longitudinally, disease progression ( N = 5) or stable stage ( N = 5) were observed. Conclusion: The TOI-based in vivo staging approach was successfully applied to bvFTD and demonstrated a plausible pattern of damage to the involved major white matter pathways. Therefore, the TOI-based staging approach may also have potential as an in vivo biomarker for bvFTD.